STRATEGI MENGEMBANGKAN BISNIS SAAT PANDEMI COFID-19 MENGGUNAKAN METODE SWOT DAN QSPM (Studi Kasus Supermarket ABC) - Cyrilla Indri Parwati; Muhammad Yusuf; Farid Nahar Fitri Andika (Universitas Sahid Surakarta, 2021)
Currently, business people are faced with various difficulties such as the number of competitors. Therefore, the company must be able to maintain in accordancewith the customer's expectations. Companies are expected to be more creative in designing and formulating business strategies, especially those that will be applied to anticipate various kinds of changes. One of the business agents is the ABCsupermarket. ABC supermarkets must have a strategy in developing their businessduring the COVID-19 pandemic so that all goods can be sold and can maintain thecustomers. The concept implemented SWOT and QSPM analysis. Previousresearch showed that the company's position was still in cell I with a total IFE value of 3.026 and an EFE value of 3.539, as well as resulted in 6 alternative business development strategies. The assessment of the QSPM matrix with thehighest TAS score of 5.125 is perfecting the management information system,human resources, and management organization.